Case of retained guide wires traversing anatomical boundaries with neurological and cardiac morbidity. Issue 1 (18th January 2022) - Omoregbee, Benjamin; Haqzad, Yama; Zicho, David; Ngaage, Dumbor
Abstract : A 69-year-old woman with a history of multiple hospital attendances for cardiac and neurological symptoms, presented with multifocal cerebral infarcts due to embolisation from retained guide wires and was referred for retrieval of two wires. One was intracardiac and the other had migrated through major vascular structures, breeching anatomical boundaries. Just before surgery, she half-expectorated a 35 cm wire that was removed with a video laryngoscope. Three days later, the second wire had traversed the right ventricular myocardium in an attempt to exteriorise, and a 7 cm wire was removed by emergency left anterior mini-thoracotomy. Her recovery was uneventful.